Evaluating FOMC forecast ranges: an interval data approach - Henning Fischer; Marta García-Bárzana; Peter Tillmann; Peter Winker (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
The Federal Open Market Committee (FOMC) of the U.S. Federal Reserve publishes the range of members' forecasts for key macroeconomic variables, but not the distribution of forecasts within this range. To evaluate these projections, previous papers compare the midpoint of the ranges with the realized outcome. This paper proposes a new approach to forecast evaluation that takes account of the interval nature of projections. It is shown that using the conventional Mincer-Zarnowitz approach to evaluate FOMC forecasts misses important information contained in the width of the forecast interval. This additional information plays a minor role at short forecast horizons but turns out to be of crucial importance for inflation and unemployment forecasts 18 months into the future. At long horizons the variation of members' projections contains information which is more relevant for explaining future inflation than information embodied in the midpoint.
Keywords: C53; E37; E58; 330; Forecast evaluation; interval data; Federal Reserve; monetary policy; Geldpolitik; Konjunkturprognose; Prognoseverfahren; Bewertung; USA